(untitled) (Cambridge, 2010)
This edited collection considers the relationship between task-based language teaching (TBLT) and technology-enhanced learning. TBLT is concerned with a number of macro-tasks such as information gathering and problem-solving as well as evaluative tasks, all of which are increasingly available via online and Web-based technologies. Technology Enhanced Learning refers to a broad conception of technology use in the language classroom and incorporates a range of interactive learning technologies such as Interactive Whiteboards and mobile learning devices.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ; Computer-assisted instruction.,Hướng dẫn sử dụng máy tính.